Morphology of Maxillary First Molars Analyzed by Cone-Beam Computed Tomography among Malaysian: Variations in the Number of Roots and Canals and the Incidence of Fusion. - Aws Hashim Ali Al-Kadhim; Zainul Ahmad Rajion; Normaliza Binti Ab Malik; Azlan Jaafar (International Islamic University Malaysia, 2024)
Vol. 22 No. 3 (2023): IIUM Medical Journal Malaysia Page (33-39)